DAMPAK MINYAK BUAH MERAH, Pandanus conoideus LAM PADA PERFORMANSI YUWANA KERAPU SUNU, Plectropomus leopardus - Titiek Aslianti; Philip Teguh Imanto; Made Suastika (Jurnal Perikanan Universitas Gadjah Mada, 2009)
Market price of coral trout grouper was increasing by the color performance of fish. Beta-carotene diet was proposed to escalate pigmentation of coral trout grouper. Red fruit oil (Pandanus conoideus, Lam) which known as potential beta-carotene source was used in coral trout diets. The dosage of 5, 2.5 and 0 ml were supplemented to the every kilogram of pellet fed as a treatment in this observation during three-month period. Three hundred and fifty juveniles with initial total length 14.28±0.2 cm and 43.41±2.62 g of body weight were stocked in fiberglass tank of 5m³ seawater. Growth data were collected monthly, while color performance was taken by digital photography at the end of observation and analyzed by "Microsoft Adobe Photoshop 8". Carotene contents in the diets and fish body result showed that the Pandanus conoideus oil has role in increasing performance of coral trout with more bright color; five ml dosage gave the best growth performance with 35.57% and 185% for total length and body weight respectively, with 90% survival rate and 1.2 feed conversion ratios.